The Comparison of Risk Factors for Stunting in Rural and City in Lampung - Aprina, Aprina; Astuti, Titi; Sanee, Aree; Erwandi, Erwandi; Shodiq, Munawar (Jurnal Kesehatan, 2023)
Globally, Rural areas have more stunted children (40%) than urban areas (33%). In contrast, in Indonesia, In 2010-2013, the prevalence of stunting in rural areas was higher than in urban areas at 40 0% and urban areas by 31.5%. This type of quantitative research uses Cross Sectional approach with the aim of study to compare risk factors for stunting in rural areas and Lampung City in 2022. The research subjects are mothers and toddlers 30 are rural, and 30 are in town. The analysis in this study used the independent t-test, Mann-Whitney, chi-square, and Fisher tests; the results showed a comparison of birth length, exclusive breastfeeding, birth spacing, economic status, and environmental factors to the incidence of stunting in cities and villages in 2022. There was no comparison of birth weight, breastfeeding for up to 2 years, depression status, number of children, parenting, dietary, and Nutrition Patterns During Pregnancy on Stunting Incidents in Cities and Villages. The dominant factors influencing stunting in cities and villages based on the results of multivariate analysis of Birth spacing. There is a comparative risk factor for stunting in both rural and urban areas in Lampung province. Stunting prevention efforts by preventing early marriage, increasing the ease of access to health services in peripheral/remote sites to reduce the distance to reach health facilities, and preventing the occurrence of Low Birth Weight Babies through various promotional efforts in preventive.